(untitled) (Journal of Scientific Research, 2014)
Mixed-ligand ternary complexes of Cu (II) metal ion with 1,2,4 triazole (TRZ) and amino acids (histidine (L1), threonine (L2), proline (L3) and hydroxyl proline (L4)) have been synthesized. The prepared ternary chelates were characterized by elemental analysis, IR and electronic spectra, as well as conductivity measurements. The general formula [Cu(TRZ)L]H2O were found for the ternary chelates containing TRZ. From the analytical and spectral data, the stoichiometry has been found to be 1:1:1 for all the complexes. A tetrahedral geometry has been proposed. Molecular modeling studies were also carried out to confirm the geometries of the complexes. All the new complexes were found to be active against bacteria. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.16993 J. Sci. Res. 6 (3), 487-496 (2014)